Highly Fluorescent Bipyrrole‐Based Tetra‐BF2 Flag‐Hinge Chromophores: Achieving Multicolor and Circularly Polarized Luminescence. (24th May 2022) - Cui, Luxia; Shinjo, Hyuga; Ichiki, Takafumi; Deyama, Koichi; Harada, Takunori; Ishibashi, Kohei; Ehara, Takumi; Miyata, Kiyoshi; Onda, Ken; Hisaeda, Yoshio; Ono, Toshikazu
Abstract: This study reports the facile syntheses of tetra‐boron difluoride (tetra‐BF2 ) complexes, flag‐hinge‐like molecules that exhibit intense green‐to‐orange luminescence in solution and yellow‐to‐red emission in the solid states. Single‐crystal structure analysis and density functional theory calculations suggested a bent structure of this series of compounds. The complexes also exhibited excellent optical properties, with quantum yields reaching 100 % and a large Stokes shift. These properties were attributed to the altered bending angle of the molecule in the S1 excited state. As the rotational motion was suppressed around the 2, 2′‐bipyrrole axis, atropisomers with axial chirality were formed, which are optically resolvable into ( R ) and ( S )‐enantiomers through a chiral column. The atropisomers thus function as circularly polarized luminescent (CPL) materials, in which the color (green, green‐yellow, and yellow) can be varied by controlling the aggregation state. This rational design of multi‐BF2 complexes can potentially realize novel photofunctional materials. Abstract : A series of tetra‐BF2 complexes with 2, 2′‐bipyrrole ligands that emit in the visible to red region in solution and in the solid state were synthesized by a one‐pot reaction. The dyes are rigid but can rotate flexibly around the bipyrrole moiety, resulting in large Stokes shifts and high quantum yields. Tuning the rotational barrier enables circularly polarized emission based on axial chirality to be achieved.